A novel retinal biomarker for Parkinson's disease: Quantifying the foveal pit with optical coherence tomography. Issue 12 (4th September 2015) - Slotnick, Samantha; Ding, Yin; Glazman, Sofya; Durbin, Mary; Miri, Shahnaz; Selesnick, Ivan; Sherman, Jerome; Bodis‐Wollner, Ivan
Abstract Background Optical coherence tomography offers a potential biomarker tool in Parkinson's disease (PD). A mathematical model quantifying symmetry, breadth, and depth of the fovea was applied. Methods Nintey‐six subjects (72 PD and 24 healthy controls) were included in the study. Macular scans of each eye were obtained on two different optical coherence tomography devices: Cirrus and RTVue. Results The variables corresponding to the cardinal gradients of the fovea were the most sensitive indicators of PD for both devices. Principal component analysis distinguished 65% of PD patients from controls on Cirrus, 57% on RTVue. Conclusion Parkinson's disease shallows the superior/inferior and to a lesser degree nasal‐temporal foveal slope. The symmetry, breadth, and depth model fits optical coherence tomography data derived from two different devices, and it is proposed as a diagnostic tool in PD. © 2015 International Parkinson and Movement Disorder Society